The Effect of Price, Positioning and Cafe Atmosphere on Consumer Satisfaction at the Janji Jiwa Cafe, Sorong City - Ratnawati Ratnawati; Wisang Candra Bintari; Digor Mufti; Rais Dera Pua Rawi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This research aims to determine if The Price, Positioning, and Suasnaa Cafe affect Customer Satisfaction at the Promise Jiwa Cafe Sorong City. The method used in this study is the quantitative method with descriptive and correlation approaches. The data was obtained by sharing questionnaires with 80 respondents—sampling techniques using the Purposive Sampling technique. The data analysis method uses multiple linear regression analysis of hypothesis testing (t-test, f-test, and determination coefficient). Researchers tested the primary data in this study by using the spss application program version 20 for windows and secondary data. The results of the research data analysis showed that price had a positive and significant effect on Consumer Satisfaction of 9.467 with a probability of 0.000. The positioning has a positive and significant effect on Consumer Satisfaction of 6,039 with a probability of 0.000. Cafe atmosphere has a positive and significant effect on Customer Satisfaction of 8,150 with a probability of 0.000. Price, Positioning, and Atmosphere Cafe are influential together (simultaneously). It indicates that all variables have a partially significant effect.